Efektivitas Pembelajaran Daring pada Mata Kuliah Media Pembelajaran Pendidikan Agama Islam - Azwir Salam (Journal on Education, 2022)
Online learning became popular in March 2020 due to the impact of the spread of the coronavirus which became a pandemic. However, the existence of online learning continues to grow. For this reason, a study was conducted to determine the effectiveness of online learning in the Learning Media course for students of the Islamic Religious Education (PAI) Department of UIN Sultan Syarif Kasim Riau. This research includes quantitative descriptive research. The research was carried out in the odd semester of the 2021/2022 academic year. The subjects of this study were 3 (three) semester PAI students who attended online lectures for the Learning Media course, consisting of three classes with a total of 73 people. Data collection techniques, namely: Observation, assignment, and test. The effectiveness analysis is guided by the guidelines for processing and determining the final value and based on certain criteria. The results of the study showed that the effectiveness of online learning in the PAI Learning Media course was very effective (95.89%). The success of online learning in PAI learning media courses is influenced by several factors, including the availability of online learning facilities and infrastructure that can be accessed by students and lecturers.